2008
DOI: 10.1159/000148244
|View full text |Cite
|
Sign up to set email alerts
|

Stereopsis and Color Vision Impairment in Patients with Right Extrastriate Cerebral Lesions

Abstract: Background and Aim: The extrastriate cortex is a visual processing structure beyond the striate cortex. This region contains cells that differ in selectivity for different features of stimuli such as color, motion and stereopsis. We studied stereopsis and color vision in patients with right extrastriate cerebral lesions. Methods: Patients with right extrastriate cerebral lesions determined by MRI were recruited among consecutive inpatients. Patients with cognitive impairment (Mini Mental Status Examination sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Two previous studies have shown that patients with schizophrenia experienced greater stereopsis deficits than healthy controls514. The generation of three-dimensional percepts has been reported to be governed by cerebral cortex, especially extrastriate cortex that abnormal activity of which has been found in patients with schizophrenia202122, which could further lead to a marked deficit of stereopsis in patients with schizophrenia. Interestingly, a recent study has found that stereopsis deficits in patients with Parkinson were associated with gray volume reduction in the right extrastriate visual cortical, which could further implicate cortical visual dysfunction in patients with Parkinson23.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies have shown that patients with schizophrenia experienced greater stereopsis deficits than healthy controls514. The generation of three-dimensional percepts has been reported to be governed by cerebral cortex, especially extrastriate cortex that abnormal activity of which has been found in patients with schizophrenia202122, which could further lead to a marked deficit of stereopsis in patients with schizophrenia. Interestingly, a recent study has found that stereopsis deficits in patients with Parkinson were associated with gray volume reduction in the right extrastriate visual cortical, which could further implicate cortical visual dysfunction in patients with Parkinson23.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical relevance of this study is related to the need for well-established normal stereoacuity ranges, with systematic control of variables, such as light intensity or undesirable movements of plates and/or head. Stereoacuity measures can contribute to the diagnosis, and the follow-up of the therapeutic management, of many ophthalmological and neurological diseases that have a high probability of impairing binocular vision, such as strabismus and amblyopia (Walraven and Janzen 1993;Lee and Isenberg 2003;Rutstein 2008;Birch and Wang 2009), cataract and pseudophakia (Jacobi et al, 2001;Lundvall and Kugelberg 2002;Hayashi and Hayashi 2004;Liu et al, 2005;Kim and Plager 2008) as well as in neurological and psychiatric diseases such as multiple sclerosis, schizophrenia, cerebral palsy and autism (Scharre and Creedon 1992;Schneider et al, 2002;Chen and Gordon 2005;Schechter et al, 2006;Kozeis et al, 2007;Koh et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…4 The process of stereopsis 4 is governed by the cerebral cortex, especially the extrastriatal cortex. 11,12 Abnormalities of steropsis have been reported in patients with supratentorial structural lesions. 12 However, the presence of stereopsis in neurodegenerative disorders has not previously been evaluated.…”
Section: Discussionmentioning
confidence: 99%